Limite, sudoeste e as vanguardas europeias: uma análise comparativa - Ribeiro, Odil Miranda (2015)
There are important visual similarities between the Brazilian movies Sudoeste (2011), by Eduardo Nunes, and Limite (1931), by Mário Peixoto. However, eighty years have passed since the production of the first film. Comparing Limite with some productions by European avant garde of the early twentieth century, it was also possible to find several visual similarities. Considering their specific conditions of production as well as their social context, this research aimed to identify and analyze these visual similarities. What could be the convergent and divergent aspects between these productions? The frame of reference for the analyses included concepts of David Bordwell e Kristin Thompson, Ismail Xavier, Jacques Aumont, André Bazin, Georges Sadoul, Laurent Jullier e Michel Marie. Specifically about intertextuality, were consulted Mikhail Bakhtin and Julia Kristeva. The concept of rhizome, defined by Gilles Deleuze and Felix Guattari, helped us to think about the language specificities of each one of the works. It could be concluded that, even considering some differences pointed out by the analyses, the two productions present existentialist content and depression behavior in the sense of the exploitation of the intimist and psychological profile of the characters, beyond structural similarities. This suggests that the film Limite has functioned, in a certain way, as a bridge between the European avant garde from the decade of 1920 and the contemporary production of the film Sudoeste.